Improving the Cognitive Learning Outcomes of Fifth-Grade Students at Ahmad Dahlan Integrated Islamic Elementary School, Jambi City, Through A Deep Learning Approach - Ferlina Azagi; M. Syahran Jailani; Kiki Fatmawati (al-Afkar, Journal For Islamic Studies, 2026)
Improving students’ cognitive learning outcomes through the implementation of the deep learning approach is considered a viable and appropriate strategy for enhancing cognitive learning outcomes in the Integrated Science subject. In its implementation, the deep learning approach must encompass the three core principles of deep learning mindful, meaningful, and joyful learning which are fully aligned with the direction of the Merdeka Curriculum. This study employs a classroom action research design with both qualitative and quantitative approaches. The research was conducted at Ahmad Dahlan Integrated Islamic Elementary School in Jambi City, with 24 fifth-grade students as the research subjects. The findings indicate that the deep learning approach can improve students’ cognitive learning outcomes. Student activity scores increased from an average of 58% in Cycle I to 85% in Cycle II. Meanwhile, improvements in students’ cognitive learning outcomes were observed, with an average score of 68.3 in the pre-cycle, increasing to 72.5 in Cycle I, and continuing to rise to 93.4 at the end of Cycle II. It can be concluded that the deep learning approach can be used as an alternative to improve students’ cognitive learning outcomes in IPAS instruction.